1995
DOI: 10.1063/1.359581
|View full text |Cite
|
Sign up to set email alerts
|

Optical and electrical properties of Ag-As-S glasses

Abstract: Physical properties of Ag2S-As2S3 glassy alloys have been studied as a function of the Ag atomic concentration x. With an increase in x, the optical-absorption edge exhibits a red shift, while the steepness of the Urbach tail changes little. In the glasses with x≥15, the electrical conductivity is governed by Ag+ ionic conduction. The ionic conductivity exponentially increases with x, and in contrast the hole conductivity hardly changes with x; however, the activation energies for the ionic and the hole conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Second, it has been demonstrated that 2.6 eV light does not produce the pattern. This is because the absorption coefficient for 2.6 eV light in the Ag-As-S film is 10 5 cm Ϫ1 , 8 so that the guided mode cannot practically propagate. Third, the ͑anti͒crater deformations can be prominent only in the direction perpendicular to the electric field of light, since the propagation of guided waves follows the Mie scattering process.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it has been demonstrated that 2.6 eV light does not produce the pattern. This is because the absorption coefficient for 2.6 eV light in the Ag-As-S film is 10 5 cm Ϫ1 , 8 so that the guided mode cannot practically propagate. Third, the ͑anti͒crater deformations can be prominent only in the direction perpendicular to the electric field of light, since the propagation of guided waves follows the Mie scattering process.…”
Section: Discussionmentioning
confidence: 99%
“…%, which were employed in the previous compositional study. 10 The glass ingots were polished to disks with a thickness of ϳ0.2 mm, and then, were annealed at the glass transition temperatures for stabilization.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the optical band gap energy decreases with an increase in the Ag content, and in AgAsS 2 it is reported to be 2.1 eV. 10 Accordingly, when such a glass is exposed to light, electrons and holes may be photoexcited, and only holes can diffuse away, which gives rise to a Dember voltage, i.e., the illuminated region being negatively charged. In response, Ag ϩ ions in unilluminated regions will migrate toward the illuminated region.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations